Absorption Line Gradients of an Elliptical Galaxy NGC 5322 - Young-Jong Sohn; Myung-Hyun Rhee; Suk-Jin Yoon (Journal of Astronomy and Space Sciences, 1999)
Archival long-slit spectra, covering the wavelength range 4050Å - 5150Å, have been used to investigate the radial behavior of absorption line features (G4300, Fe4383, Ca4455, Fe44531, Fe4668, and Hα) of an eliptical galaxy NGC 5322. The heliocentric recession velocity of NGC 5322 has been derived as 1888+/-51 km s-1. Metallic absorption lines of NGC 5322 show significant radial gradients through the major axis. The minor axis shows much smaller radial metal line gradients than the major axis. The mean slopes of Fe line gradients to the major and minor axes of NGC 5322 were estimated as -0.433+/-0.064 and -0.242+/-0.096, respectively. Significant radial gradients of Hα absorption of NGC 5322 are also detected both on the major and minor axes. It is shown that the radial metallicity gradients in NGC 5322 are smaller than expected in a simple dissipative collapse model. Rather, dissipationless collapse, such as hierarchical merhing, could have contributed during the initial stage of the galaxy formation.